RACISM AS MANIFESTATION OF WHITE SUPREMACY IN BLACKKKLANSMAN AND 13TH FILMS - Bachron, Alfa Sebastian; Hkikmat, Mahi Mamat; Nurrachman, Dian (CALL, 2023)
This research aimed to present how white supremacy was represented in 13th by Ava DuVernay and BlacKkKlansman by Spike Lee and to identify and analyse how the characters in 13th by Ava DuVernay and BlacKkKlansman by Spike Lee deal with the racist system. According to Abrams literary criticism is a method to describe events in the film. Seek to understand and interpret the meaning of an event of human behaviour interaction in a particular situation according to the researcher's perspective. Research that literary criticism aimed to understand the literary object under study in depth. The method used was to explore sources of information and data in the form of popular literature, which is films. Using a postcolonial approach, both films had a theme of racism, and also white supremacy in the USA. The issue of racism and white supremacy has resurfaced after more and more cases of racism by white people against black people. The characters in both films find racism from white people, they will try to fight against racism with various kinds of struggles.Â Keywords: postcolonialism, racism, white supremacy